2015
DOI: 10.1111/jen.12269
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes associated withIps cembrae(Coleoptera: Curculionidae): comparison of generations, sexes and sampling methods

Abstract: A study of nematodes associated with the large larch bark beetle Ips cembrae (Heer 1836) was carried out at three locations in the Czech Republic. The proportion of beetles infested by endoparasitic nematodes (representatives of genera Contortylenchus, Parasitylenchus, Cryptaphelenchus and Parasitorhabditis) ranged from 29.9 to 50.9%. Significant differences were determined in nematode infestation levels among locations, generations and sampling methods. No differences were found in infestation rates between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The present study confirmed the co‐occurrence of two phoretic nematode species, T. synpapillata and M. macrospiculum , associated with RPW at all sampling sites (Troccoli et al, ) and provided information regarding other nematodes potentially associated with RPW in southern Italy. Individual insects can simultaneously harbor more than one nematode genus (Grucmanová, Holuša, Čermák, & Nermut, ; Kanzaki et al, ; Shimizu et al, ); R. palmarum and R. cruentatus are reported to host several nematode associates, including Teratorhabditis and Mononchoides spp. (Esparza‐Diaz et al, ; Kanzaki et al, , , ; Mazza et al, ; Sudhaus et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study confirmed the co‐occurrence of two phoretic nematode species, T. synpapillata and M. macrospiculum , associated with RPW at all sampling sites (Troccoli et al, ) and provided information regarding other nematodes potentially associated with RPW in southern Italy. Individual insects can simultaneously harbor more than one nematode genus (Grucmanová, Holuša, Čermák, & Nermut, ; Kanzaki et al, ; Shimizu et al, ); R. palmarum and R. cruentatus are reported to host several nematode associates, including Teratorhabditis and Mononchoides spp. (Esparza‐Diaz et al, ; Kanzaki et al, , , ; Mazza et al, ; Sudhaus et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirmed the co-occurrence of two phoretic nematode species, T. synpapillata and M. macrospiculum, associated with RPW at all sampling sites (Troccoli et al, 2015) and provided information regarding other nematodes potentially associated with RPW in southern Italy. Individual insects can simultaneously harbor more than one nematode genus (Grucmanová, Holuša, Čermák, & Nermut, 2015;Kanzaki et al, 2011;Shimizu et al, 2013); (Félix, 2006;Kanzaki & Giblin-Davis, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why nematodes were the dominant parasite at some localities and why levels of infection were very low in the current study relative to those reported for Ips spp. (Grucmanová & Holuša 2013;Grucmanová et al 2014Grucmanová et al , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Although antagonists of I. typographus is well known, their effects on beetle reproductive success have most often been studied in the laboratory, and their effects on population densities in the eld are largely unknown 26,27 . Natural enemies of I. cembrae have been infrequently studied [28][29][30] and their effects on I. cembrae abundance and fecundity are largely unknown. Pathogens, nematode parasites, and parasitoids of bark beetles are taxonomically diverse, and may, in some cases, cause serious pathological and behavioral changes in their hosts [31][32][33] .…”
Section: Introductionmentioning
confidence: 99%